Dynamic event-triggered cooperative formation control for UAVs subject to time-varying disturbances - Wei, Lili; Chen, Mou; Li, Tao (IET control theory & applications, 2020)
The dynamic event-triggered cooperative formation control problem for unmanned aerial vehicles (UAVs) subject to time-varying disturbances is studied. A single UAV is described by a second-order kinematical model and the desired formation is constructed by utilising the leader–follower framework, in which the leader UAV provides the desired trajectory for each follower. Unknown external disturbances are assumed to be composed of multiple frequency waves and appropriate disturbance observers are designed. A dynamic event-triggered mechanism is proposed with its triggering threshold being dynamically adjustable rather than a fixed constant, which can reduce data transmissions more effectively and meanwhile avoid the Zeno behaviour. Then a distributed event-triggered control scheme is developed for the UAV formation and two sufficient conditions on asymptotical stability of the resulting closed loop system are derived. Furthermore, controller gains, observer gains, and triggering parameters can be jointly obtained by solving the desired linear matrix inequality (LMI). Finally, a simulated example is given to illustrate the obtained results.